5 Reflections on Trans* & Taxonomy (with Neo Musangi). Issue 4 (3rd July 2016) - Macharia, Keguro
Abstract: This reflection juxtaposes African queer studies and visual studies to consider how African queerness is represented. Taking the work of Kenyan photographer Neo Musangi as its point of departure, it foregrounds questions raised by representations of trans individuals about the politics of knowledge and the ethics of opacity. As trans activists and intellectuals have noted, the visual is an especially vexed site of gendered policing, and I consider how quotidian habits of visual analysis risk performing similar policing. Instead of situating trans visual art and activism as exceptional, as requiring special analytic tools, I argue that it teaches us to re-think our assumptions about all African art, refusing to take for granted gendered, sexed, and sexualised categories and practices.